2015
DOI: 10.5194/isprsarchives-xl-7-w3-1177-2015
|View full text |Cite
|
Sign up to set email alerts
|

Data Validation and Case Studies using the TET-1 Thermal Infrared Satellite System

Abstract: ABSTRACT:Based on the DLR satellite system BIRD, launched and operated in the early 2000, the TET-1 satellite has been launched in 2012 as part of the FireBird satellite constellation. The constellation will consist of two satellites, the second one to be launched in the first half of 2016. Acquired imagery is processed and archived by DLR and will be publicly available. For this purpose, a processing chain has been implemented converting raw data (level 0 product) to geo-annotated at-sensor radiance (level 1b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Together they will provide one dataset per day. BIROS is still not operational, but its basic characteristics are almost identical to TET-1 (Table 1; for further details on the TET-1 mission see Lorenz et al [30] and Fischer et al [32]). We have ascertained that FireBird satellites have one important advantage over other satellite instruments-their on-board processing allows repeated acquisition over the same area within a few microseconds, thus preventing data saturation.…”
Section: Tet-1mentioning
confidence: 99%
“…Together they will provide one dataset per day. BIROS is still not operational, but its basic characteristics are almost identical to TET-1 (Table 1; for further details on the TET-1 mission see Lorenz et al [30] and Fischer et al [32]). We have ascertained that FireBird satellites have one important advantage over other satellite instruments-their on-board processing allows repeated acquisition over the same area within a few microseconds, thus preventing data saturation.…”
Section: Tet-1mentioning
confidence: 99%
“…Satellite imagery is an important tool for fire management and strategic fire intelligence that can cover large swaths of territory and detect medium to large fires based on automated or semi-automated algorithms. There are notable exceptions where certain experimental (e.g., BIRD, TET-1; [ 5 , 6 ]) and operational (SUOMI-NPP, VIIRS; [ 7 , 8 ]) satellites are capable of detecting very small fires. However, satellite visit periods are often too infrequent and image resolution inadequate for detection of fires when they are small and developing.…”
Section: Airborne Sensor Platformsmentioning
confidence: 99%
“…Section 2.1 provides more details on TET-1. Fischer et al [31] demonstrated the high temperature event detection capabilities of TET-1 by showing the detection of the volcanic hotspot at the 22 February 2015 acquisition as one example. Zakšek et al [32] investigated the August-November 2014 Stromboli Volcano eruption by combining TET-1 imagery and thermal ground-based observations.…”
Section: Villarrica Volcanomentioning
confidence: 99%